Scenarios of a desirable and fair energy transition - Ewa Dönitz; Barbara Breitschopf; Uta Burghard (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2023)
The paper was created in the context of the project Akzept and focuses on the description of the scenario process and its results in the form of three scenarios for a desirable energy transition. The project aimed at analysing the influence of participation, communication, and selected socioeconomic criteria on the acceptance of the energy transition. The impact of self-supply of electricity and membership in a citizen energy initiative on the acceptance of the energy transition by those who did not participate in this way was also studied. The team conducted two scenario workshops to describe future designs of the energy transition as well as the needs and preferences of society in the form of various future scenarios. One workshop included persons who participated in the form of self-supply or membership in energy initiatives, while the other workshop aimed at socalled non-participants with a general interest in the topic of energy. The workshops comprised a combination of different activities, brainstorming, and discussions in small groups, and contributed to ensure engagement of participants with very different backgrounds throughout the scenario development. The scope for the scenario process was formed by important topics related to the energy transition that can be divided into three groups: individual engagement and decisions, energy transition in the broader context, and involvement as well as decisions in general. The energy transition can be achieved along three different paths, so-called scenarios: bottom-up, acceleration, and passive. The bottom-up scenario emphasises decentralised energy production with transparency and fairness, allowing for genuine participation and co-determination of citizens. It involves many small plants for energy production and allows for self-consumption, with low barriers for citizens to participate. The acceleration scenario prioritises rapid implementation and focuses on becoming independent from energy imports. It places a strong emphasis on regulations, and companies that emit high levels of CO2 have to pay a high price for their emissions. The passive scenario is characterised by a low level of interest from citizens, who display weak acceptance towards the energy transition. Information and transparency are not important, and the government is responsible for deciding on how to achieve the energy transition. The transition occurs at low cost, and energy utilities provide renewable energy at low prices.
Keywords: 330; foresight; scenarios; participation; energy transition; acceptance